Social Support and Subjective Well-Being in Chinese Parents of Children With Autism Spectrum Disorder: The Mediating Role of Perceived Discrimination - Ban, Yongfei; Sun, Ji; Liu, Jiang (Frontiers in Psychology, 2021)
The present research was done to examine whether social support was related to subjective well-being on Chinese parents of children with autism spectrum disorder (ASD) and how perceived discrimination affected this relationship. Two hundred four parents with ASD children were investigated by Inventory of Social Support Behavior, Perceived Discrimination Scale for Parents of Children With ASD, Subjective Well-being Scale. The results showed that perceived discrimination was negatively associated with social support and subjective well-being, and social support was positively related to subjective well-being. Furthermore, perceived discrimination played a partial mediating role between social support and subjective well-being. All the findings suggest that social support can directly influence subjective well-being of parents of ASD children and indirectly influence subjective well-being through perceived discrimination.